Harmonization of Prisoners’ Rights in National Law in Accordance with Global Standards - Richard Chandra Adam; Amad Sudiro; Luo Yuan Yuan (Universitas Negeri Semarang, 2025)
This study is grounded in the principle that human rights are inherent and cannot be separated from individuals under any circumstances, including those serving prison sentences. Although imprisonment restricts personal liberty, it does not eliminate basic rights; however, violations of prisoners’ rights remain widespread globally and within Indonesia, including overcrowded and degrading prison conditions, forced labor practices, and inadequate access to healthcare, education, and legal aid. The research examines how international legal instruments regulate the protection of prisoners’ rights and how these standards are implemented within Indonesia’s correctional system. Employing a normative legal research method with a statutory approach, the study draws upon primary legal sources, such as international conventions and national legislation, as well as secondary materials consisting of academic writings, journal articles, and official reports. The findings indicate that several international instruments establish universal standards for the treatment of prisoners, including the Universal Declaration of Human Rights (1948), the International Covenant on Civil and Political Rights (1966), the Convention against Torture (1984), the Nelson Mandela Rules, and the Bangkok Rules for women prisoners. Indonesia has ratified key conventions and possesses a comprehensive domestic legal framework, including the 1945 Constitution, Pancasila, and Law Number 22 of 2022 on Corrections. Nonetheless, practical implementation remains limited due to persistent prison overcrowding, insufficient health facilities, unmet gender-specific needs of women prisoners, and the absence of ratification of the Optional Protocol to the Convention against Torture (OPCAT). The study concludes that despite strong normative foundations, there remains a significant gap between legal standards and correctional realities, and recommends ratifying the OPCAT, increasing correctional resources, strengthening rehabilitation-based programs, and adopting gender-responsive prison policies to align national practice with international human rights norms.